Uptake Pathway of Polyomavirus via Ganglioside GD1a - Gilbert, Joanna (American Society for Microbiology, 2004)
The pathway of entry of polyomavirus (Py) has been investigated with glycolipid-deficient C6 cells and added ganglioside GD1a as a specific virus receptor. Unsupplemented C6 cells show a low basal level of infection but become highly infectable by Py following preincubation with the sialic acid-containing ganglioside GD1a (38). Addition of GD1a has no effect on the overall level of virus binding but mediates the internalization and transit of virus to the endoplasmic reticulum (ER). This pathway of entry is cholesterol and caveola dependent and requires intact microtubules as well as a dynamic state of the microfilament system. In contrast to vesicular transport of other cargo via glycolipids, Py particles do not appear to pass through the Golgi apparatus. Colcemid and brefeldin A block transport of the virus to the ER in GD1a-supplemented cells and lead to accumulation of virus in a caveolin-1-containing environment. Several features distinguish the efficient GD1a-mediated pathway of virus uptake from the less-efficient pathway of basal infection in C6 cells.